Teleological Ethics and the Moral-Legal Justification of Abortion: A Utilitarian Perspective - Salsabila; M. Razkiazka M H. (Jurnal Cakrawala Akademika, 2025)
This study examines the moral and legal justification of abortion through the lens of teleological ethics, particularly utilitarianism. Employing a qualitative methodology, it analyzes classical philosophical texts, contemporary academic literature, and legal frameworks to assess how outcome-based ethical reasoning informs abortion debates. Findings indicate that utilitarian ethics support abortion access as a means to reduce suffering and enhance societal well-being, especially for marginalized populations. However, the analysis also acknowledges critiques concerning the moral status of the fetus and the limitations of purely consequentialist approaches. The study concludes that while teleological ethics provide a flexible framework for evaluating abortion, integrating deontological principles may offer a more comprehensive ethical discourse.